Patient satisfaction & cardiovascular risks among patients attending Klinik Rawatan Keluarga, Hospital USM - Abd.Aziz, Masseni (2015)
Introduction: Cardiovascular disease (CVD) accounted for 30% of an estimated 58 million death globally from all causes in 2005 and death due to non-communicable disease (half from CVD) is expected to increase by 17% from 2006 to 2015 (1). Objective: To evaluate patient satisfaction, modifiable cardiovascular risk factors and their relationship after 6 months follow up among moderately-high cardiovascular risk patient attending Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia (USM) . Material and method: A cross sectional study and prospective study was conducted among patient with moderately-high cardiovascular (CV) risk patient attending KRK, USM hospital, Kelantan. Patient with moderately-high CV risk underwent structured counseling on CV risk prevention and their satisfaction to the doctor-patient interaction was assessed using SKIP 11, patient was also assessed on their modifiable CV risk (SBP, TC & HDL) at baseline and at 6 months post counseling to see the changes in the outcome. The association between satisfaction and outcome were evaluated. Descriptive analysis, paired t test and general linear regression were used using PASW version 19. Result: A total of 104 patients responded giving a response rate of 98.1%. 76.5% of the patient was satisfied with doctor-patient interaction with the favorable domain of distress relief (85.3%) and rapport (91.2%). The unfavorable domain was interaction outcome with only 67.6% patient satisfied in this domain. There were also significant changes in the modifiable CV risk namely total cholesterol (TC) p<0.022 and systolic blood pressure (SBP) p<0.001 after 6 months post intervention counselling. However, there was no relationship between patient satisfaction and changes in modifiable cardiovascular risk. Conclusion: With the use of structured cardiovascular risk prevention counseling based on WHO (2007) guideline, majority (three quarter) of moderately-high risk CV patients showed satisfaction in doctor-patient interaction, specifically in terms of distress relief and rapport. Even though there is improvement in the modifiable risk factors namely SBP and TC at 6 months follow-up, however this changes were not related with the patients’ satisfaction. It can be concluded that the improvement of modifiable CV risk factors studied do not solely result from single intervention counselling but can be contributed by many factors such as content of intervention counselling, drug dosage adjustment, frequent medical visit and compliance intent.